2016
DOI: 10.1007/s10096-016-2654-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome diversity in the sputum of patients with pulmonary tuberculosis

Abstract: TB is a worldwide pandemic. India has the highest burden of TB, with WHO statistics for 2013 giving an estimated incidence figure of 2.1 million cases for India out of a global incidence of 9 million. Microbiota have been shown to be associated with many disease conditions; however, only few studies have been reported for microbiota associated with TB infection. For the first time, we characterized the composition of microbiota of TB patients of India, using high-throughput 16S rRNA gene sequencing and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
77
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 22 publications
12
77
2
1
Order By: Relevance
“…For instance, Yu et al [22] reported that the lung tissue microbiota showed increased alpha diversity with environmental exposures such as air particulates, residence in high population density areas, and pack-years of tobacco smoking. Krishna et al [23] showed the presence of diverse opportunistic pathogenic microbiota in TB patients increased the complexity and diversity of sputum microbiota. Paganin et al [20] detected that changes of microbial community in CF airway were relevant to a severe decline of lung function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Yu et al [22] reported that the lung tissue microbiota showed increased alpha diversity with environmental exposures such as air particulates, residence in high population density areas, and pack-years of tobacco smoking. Krishna et al [23] showed the presence of diverse opportunistic pathogenic microbiota in TB patients increased the complexity and diversity of sputum microbiota. Paganin et al [20] detected that changes of microbial community in CF airway were relevant to a severe decline of lung function.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] In previous studies, it has been found that the microbial community of lung could be changed due to alerted microenvironment of lung, which may result from diseases or external environmental disturbance. [4,[14][15][16][17][18][19][20][21][22][23] In the case of CF, mutations in CFTR can change the ion flux, impact the normal airway function, and compromise the normal innate immune defense finally, making the lower airways easier to be infected. Although typically only a few species are associated with chronic airway infections in CF, along with the improved treatments of infections, new species associated with CF has emerged, and the total microbes should be took into account as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis revealed more Proteobacteria and Bacteroidetes in TB samples and more Firmicutes in controls with similar coughing symptoms [187]. In contrast, another study reported that the relative abundance of Firmicutes and Actinobacteria was significantly higher in TB samples [188]. The presence of certain bacteria and the disturbance of the lung microbiota may be associated with not only the onset of TB but also disease recurrence and treatment failure [189].…”
Section: Microbiome and Tbmentioning
confidence: 99%
“…Improved strategies and methodological harmonization are required to advance this research field. Several authors have described changes of the lung microbial communities upon M. tuberculosis infection though with variable outcomes [172][173][174][175][176][177] likely reflecting inter-individual differences between patients. Importantly, also anti-TB therapy causes changes in microbiota compositions [170,172,178].…”
Section: Microbiome Guided Treatment Perspectivesmentioning
confidence: 99%